Mental Health Literacy of Non-mental Health Nurses: A Mental Health Survey in Four General Hospitals in Hunan Province, China - Hao, Yuzhu; Wu, Qiuxia; Luo, Xiaoyang; Chen, Shubao; Qi, Chang; Long, Jiang; Xiong, Yifan; Liao, Yanhui; Liu, Tieqiao (Frontiers in Psychiatry, 2020)
Background: The high numbers of patients with mental illness, especially those who are misdiagnosed or delayed in treatment in China, have imposed a huge burden on the country and the society. This study was designed to investigate the mental health literacy (MHL) of non-mental health nurses. Method: A cross-sectional survey was designed, and a convenient cluster sampling method was applied. We presented evidence on 601 nurses from the non-mental health department in four hospitals in Hengyang city, China. One-third of the vignettes were diagnosed with schizophrenia, depression, or generalized anxiety disorder (GAD). Result: The correct identification rates for schizophrenia, depression, and GAD vignettes reached 38.9, 56.2, and 17.5%, respectively. The majority of the participants deemed that the person in each vignette needed professional help, and most of them preferred professional medical help and lifestyle interventions. As for the likely outcome for the persons described in each vignette, more than half of the participants thought that with professional help, the patients would make a full recovery, but problems would probably recur. Conclusion: The MHL of non-mental health nurses is insufficient in China. This condition is particularly applicable in the case of GAD. Thus, the country must implement more mental health education programs to improve the MHL of non-mental health nurses.